2021
DOI: 10.1088/1681-7575/abe0fc
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for the dimensionally consistent treatment of angle and solid angle by the International System of Units (SI)

Abstract: Because of continued confusion caused by the SI's interpretation of angle and solid angle as dimensionless quantities (and the radian and steradian as dimensionless derived units), it is time for the SI to treat these dimensional physical quantities correctly. Building on previous authors' foundations, starting from Euclid's Elements, I argue that angle should be recognized as a base quantity with an independent dimension: angle, A. A dimensionally consistent analysis of rotational geometry and mechanics resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
(136 reference statements)
0
15
0
Order By: Relevance
“…Various advantages of giving plane angles independent, dimensional status, rather than the dimensionless status that was formally adopted within the SI in 1995, have been set out many times over a long period [e.g. [8,9,[11][12][13][14]]. Such advantages are implicitly already recognised within the SI for quantities such as radiant intensity and radiance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various advantages of giving plane angles independent, dimensional status, rather than the dimensionless status that was formally adopted within the SI in 1995, have been set out many times over a long period [e.g. [8,9,[11][12][13][14]]. Such advantages are implicitly already recognised within the SI for quantities such as radiant intensity and radiance.…”
Section: Discussionmentioning
confidence: 99%
“…Since this paper was written, Brian Leonard's long, thoughtful and well-researched paper on the topic, Proposal for the dimensionally consistent treatment of angle and solid angle by the international system of units [14], has been accepted for publication. Although there is a great deal of common ground, it will probably be helpful to readers to highlight the main differences between his proposal and the one put forward here.…”
Section: Note Added After Submissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendation 1 of the CIPM 1980 was not accepted positively by all, see, for example, [5]. Recently, an increasing number of researchers come to the idea that the plane angle is a dimensional quantity, and the radian is not a dimensionless number one [6][7][8][9][10][11]. In [10], proceeding from the laws of physics and using rigorous mathematical calculations, it was shown that the plane angle does not depend on any physical quantity, has its own nonzero dimension, which, following [5,11], we will denote by the symbol A.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of researchers come to the idea that the plane angle is a dimensional quantity, and the radian is not a dimensionless number one [6][7][8][9][10][11]. In [10], proceeding from the laws of physics and using rigorous mathematical calculations, it was shown that the plane angle does not depend on any physical quantity, has its own nonzero dimension, which, following [5,11], we will denote by the symbol A. This approach is fully consistent with the metrological rules for determining the dimensions of derived quantities and their units [3].…”
Section: Introductionmentioning
confidence: 99%